Prevalence of depression, anxiety and stress among school going adolescents in Delhi: a cross sectional study - Kumar, Ashok; Yadav, Geeta; Chauhan, Nitesh; Bodat, Suman (International Journal Of Community Medicine And Public Health, 2019)
Background: Adolescence is a stressful period due to physical, psychological, sexual changes and the presence of psychiatric disorders such as depression, anxiety and stress at this stage of life is a matter of concern. Depression is a common mental disorder, characterized by persistent sadness and a loss of interest in activities that you normally enjoy, accompanied by an inability to carry out daily activities, for at least two weeks. The objective of this study is to find the prevalence and associated factors of depression, anxiety and stress among school going adolescents. Methods: This was a school based descriptive cross-sectional study conducted in the month of July 2018 in an urban school in New Delhi. A semi-structured, self-administered questionnaire to assess socio-demographic profile as well as depression anxiety stress scale (DASS)–21 was used to assess depression, stress and anxiety. Results: Overall prevalence of depression, anxiety and stress were found to be 47.9%, 65.3%, and 51.8% respectively. Most of student suffered from moderate depression (46.8%), anxiety (33.3%) and mild stress (60.9%). It was noted that these were more common among female students, late adolescent age group, students alone/ away from family, students from separated/ single parents, consuming alcohol and family pressure to perform well in school. Conclusions: The alarming risk of depression, anxiety and stress among students with low academic satisfaction as well as those who face family pressure to perform better calls for need of parents-student counselling sessions, as well as frequent extracurricular activities to help create a healthier school environment.